The challenges of student voice in primary schools: Students 'having a voice' and 'speaking for' others. Issue 2 (August 2019) - Mayes, Eve; Finneran, Rachel; Black, Rosalyn
Student participation in school decision-making and reform processes has taken inspiration from reconceptualisations of childhood. Advocates for student voice argue for the repositioning of children and young people in relation to adults in schools. This article works with data from a multi-sited case study of three primary schools and students', teachers' and school leaders' accounts of their student voice practices. We consider the relationships between students in student voice activities in primary schools, and the possibilities and ambivalences of representative students 'speaking for' other students. We integrate recent insights from moves beyond voice in childhood studies, and from the turn to listening in cultural studies, and raise questions for students, teachers and researchers who seek to encourage student voice in primary schooling.